Fatores de risco associados a acidente vascular encefálico em pós-operatório de cirurgia cardíaca: um estudo de coorte - Marchesan, Luana Quintana (2022)
Despite improvements in the healthcare system, cardiovascular diseases are still the leading cause of death in the adult population. For every ten deaths in this population, three are related to cardiovascular disease, and ischemic heart disease or coronary artery disease (CAD), is responsible for most of these deaths. Treatment of CAD has advanced with the development of new medications and the advent of coronary artery bypass grafting (CABG) in the 1960s. These technologies provided more remarkable survival and quality of life for many patients. However, heart surgery is not without risk. Among its complications is the stroke, a rare complication (1- 6% of cases) but feared since it causes significant morbimortality and high hospital and social costs. This study aimed to evaluate predictors of postoperative stroke in patients undergoing cardiac surgery at the University Hospital of Santa Maria (HUSM). To this end, a retrospective cohort study was carried out, which included an analysis of 678 patients ≥ 18 years old who underwent valve replacement surgery and/or coronary artery bypass grafting from July 1, 2011, to December 31, 2018. In addition, demographic data, exams, data and clinical information from the postoperative period were collected. The incidence of stroke in the sample was 3.5% (n=24), with most events being ischemic (n=23) and diagnosed within the first 72 postoperative hours (n=21). After univariate and multivariate analysis, the following risk factors related to postoperative stroke were identified: previous stroke/TIA (RR=2.7 - 95% CI 1.108 -6.559 - p < 0.029), carotid disease (RR=4.0 – 95% CI 1.429-11.440 – p < 0.008), previous atrial fibrillation (RR=3.1 – 95% CI - 1.209-7.935 – p < 0.019) and postoperative platelets ≥ 230 thousand (RR=2.5 – 95% CI - 1.059 -5.882 - p < 0.037). Hospital mortality was 8.0% (N=54), with 20.8% in patients who had a stroke in the postoperative period. The incidence of stroke found in the sample was higher than that described in the world literature, but similar to the national series and the individuals who presented this complication had higher mortality. This study also reinforces classic risk factors for postoperative stroke in cardiac surgery.